Early Childhood Education Teachers in Indonesia: Validity and Reliability of Preschool Child Development Surveillance Instruments - Maghfuroh, Lilis; Salimo, Harsono; Qadrijati, Isna; Subiyanto, A.A (Migration Letters, 2023)
The purpose of this study was to test the validity and reliability of preschool development surveillance instruments that researchers had made. There were 3 instruments tested for validity and reliability, namely a developmental surveillance instrument aged 36-48 months, a surveillance instrument aged 49-60 months, and a surveillance instrument aged 61-72 months. In each instrument, there are 7 indicators of child development, namely the development of gross motor, fine motor, language, personal social, religious, and moral values, cognitive, and art. Each indicator consists of 2-item questions, so the total number of questions in the instrument is 14 for each. validity test using the product moment test and reliability test using the alpha Cronbach coefficient test with data analysis using SPSS for Windows 26. Surveillance instruments for the development of preschool children aged 36-48 months, 49-60 months, and 61-72 months have high reliability and good validity in assessing the development of preschool children at the level of surveillance carried out by early childhood education teachers so that their use can be expanded.